2020
DOI: 10.1136/bmjgh-2020-003033
|View full text |Cite
|
Sign up to set email alerts
|

Not just money: what mothers value in conditional cash transfer programs in India

Abstract: IntroductionConditional cash transfers (CCTs) have become an important policy tool for increasing demand for key maternal and child health services in low/middle-income countries. Yet, these programs have had variable success in increasing service use. Understanding beneficiary preferences for design features of CCTs can increase program effectiveness.MethodsWe conducted a Discrete choice experiment in two districts of Uttar Pradesh, India in 2018 with 405 mothers with young children (<3 years). Respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…(49,50). Studies have shown that cash incentives play a role in purchasing food items that are perceived as costly or not purchased by households regularly (51). Our study also aligns with this argument and provides substantial evidence that cash incentives promote a higher purchase power for protein-rich items among our targeted population.…”
Section: Discussionsupporting
confidence: 84%
“…(49,50). Studies have shown that cash incentives play a role in purchasing food items that are perceived as costly or not purchased by households regularly (51). Our study also aligns with this argument and provides substantial evidence that cash incentives promote a higher purchase power for protein-rich items among our targeted population.…”
Section: Discussionsupporting
confidence: 84%
“…Given the massive investment by the Indian government and the high uptake of maternal services in recent years, it is critical to utilisation and non-utilisation of safe-motherhood services in the country. Previous studies highlight the negligence of complete antenatal care, deficiency in skilled birth attendants during delivery, and high cost of maternal healthcare resulting in high MMR [16][17][18][19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…This study has be designed according to the guidelines written by Lancsar&Louviere(2008) [21]. In this study, based on the analysis of policy documents and the review of literature in related elds [22][23][24], several attributes were initially selected as key attributes in uencing the willingness and preference of people with severe mental disorders to participate in social healthcare policies in Beijing. The attributes were then evaluated and the level rating of each attribute was developed through expert consultation, while the expert group was formed that included three professors of health economics, two psychiatrists from hospitals, and two psychiatrists from communities institutions.…”
Section: Determination Of Attributes and Levelsmentioning
confidence: 99%